The story so far………- current opinion in the use and applications of interactive storytelling in physiology and clinical education - Bagley L.; Wilson J.; Kime A. (Current Research in Physiology)
Physiology and clinical practice are subjects of study which demand integration of multiple sources of systems working knowledge and information on the performance of those systems to come to meaningful conclusions. This is made more complex by the interpretation and actions as a result of this conclusion having direct impact on the sum of the component systems, the human, thereby integrating significant social and psychological considerations into an already complex situation.As higher education educators, it is a significant challenge to provide our learners with training and most importantly, practice, in these knowledge, skills and behaviours in the classroom. There has been a significant interest in recent years in providing active learning opportunities which allow learners to apply subject knowledge to multi-faceted, immersive, continuously evolving stories which reflect a graduate's professional aspirations. This review highlights practices from the literature of storytelling education which the higher education educator can utilise in promoting “meaning making” in the classroom. Here, the case for interactive storytelling in physiology and clinical education is argued, as well as presenting commonly utilised techniques and practices with which educators can embed storytelling into their pedagogy as well as highlighting future directions in this field.